Gene Expression in the Salivary Gland of Rhipicephalus (Boophilus) microplus Fed on Tick-Susceptible and Tick-Resistant Hosts - Giachetto, Poliana Fernanda; Cunha, Rodrigo Casquero; Nhani, Antônio; Garcia, Marcos Valerio; Ferro, Jesus Aparecido; Andreotti, Renato (Frontiers in Cellular and Infection Microbiology, 2020)
The success of cattle tick fixation largely depends on the secretion of substances that alter the immune response of the host. The majority of these substances are expressed by the parasite salivary gland and secreted in tick saliva. It is known that hosts can mount immune responses against ticks and bovine European breeds, and bovine industrial crossbreeds are more susceptible to infestations than are Bos indicus cattle. To identify candidates for the development of novel control strategies for the cattle tick Rhipicephalus (Boophilus) microplus, a salivary gland transcriptome analysis of engorged females fed on susceptible or resistant hosts was performed. Using RNA-Seq, transcriptomes were de novo assembled and produced a total of 235,451 contigs with 93.3% transcriptome completeness. Differential expression analysis identified 137 sequences as differentially expressed genes (DEGs) between ticks raised on tick-susceptible or tick-resistant cattle. DEGs predicted to be secreted proteins include innexins, which are transmembrane proteins that form gap junction channels; the transporters Na+/dicarboxylate, Na+/tricarboxylate and phosphate transporter and a putative monocarboxylate transporter; a phosphoinositol 4-phosphate adaptor protein; a cysteine-rich protein containing a trypsin inhibitor-like (TIL) domain; a putative defense protein 3 containing a reeler domain; and an F-actin-uncapping protein LRRC16A with a CARMIL_C domain; these genes were upregulated in ticks fed on tick-susceptible cattle. DEGs predicted to be non-secreted proteins included a small heat shock protein and the negative elongation factor B-like, both acting in a coordinated manner to increase HSP transcript levels in the salivary glands of the ticks fed on tick-susceptible cattle; the 26S protease regulatory subunit 6B and another chaperone with similarity to calnexin, also upregulated in ticks fed on tick-susceptible cattle; an EF-hand calcium binding protein and a serine carboxypeptidase (SCP), both involved in the blood coagulation cascade and upregulated in ticks fed on tick-susceptible cattle; and two ribosomal proteins, the 60S acidic ribosomal protein P2 and the 60S ribosomal protein L19. These results help to characterize cattle tick salivary gland gene expression in tick-susceptible and tick-resistant hosts and suggest new putative targets for the control of tick infestations, as those genes involved in the mechanism of stress response during blood feeding.